Assessment of resource-saving technologies in low-tonnage chemical industries for compliance with best available technologies principles - N. A. Kostikova; E. N. Glukhan; P. V. Kazakov; M. M. Antonova; D. I. Klimov (Тонкие химические технологии)
Objectives. To develop a methodology for the quantitative assessment of new technologies in accordance with the principles of best available technologies (BAT). To evaluate the developed technologies of low-tonnage chemical production of tetramethylthiuram disulfide, N-cyclohexyl-2- benzothiazolylsulfenamide, diisopropyl xanthohen disulfide, and N-phenyl-2-naphthylamine for compliance with BAT principles and compare with alternative (implemented, known) technologies in terms of environmental impact.Methods. A methodology for the quantitative assessment of new technologies for the production of organic substances in accordance with BAT principles was used.Results. The developed methodology for the quantitative assessment of new technologies in accordance with BAT principles based on the calculation of comprehensive comparison indicators with alternative technologies for technological and environmental indicators allowed us to determine the level of implemented technologies for the production of tetramethylthiuram disulfide, N-cyclohexyl-2-benzothiazolylsulfenamide, diisopropyl xanthohen disulfide, and N-phenyl-2- naphthylamine to minimize the impact on the environmental, including through the development of special technological solutions for resource conservation and waste reduction, and to conduct a quantitative assessment of the achieved environmental outcome. It is established that the considered new technologies of low-tonnage chemical production comply with BAT principles and are more environmentally advanced compared to alternative ones previously implemented in the USSR.Conclusions. For the first time, a methodology for quantifying new technologies in accordance with BAT principles is proposed. The possibility of its use at the stage of making basic technological decisions on the implemented production method in order to ensure compliance with legislative requirements for technologies in the field of environmental safety to achieve environmental protection goals is shown on the example of low-tonnage technologies for the production of tetramethylthiuram disulfide, N-cyclohexyl-2-benzothiazolylsulfenamide, diisopropyl xanthohen disulfide, and N-phenyl-2-naphthylamine created in GosNIIOKhT.